Sistem Informasi Inventaris Aset Berbasis Website di PT Dosni Roha Cabang Medan - Ginting, Riah Ukur; Yulirianto Nduru; Burhanuddin Damanik; Dini M Hutagalung (Universitas Sari Mutiara Indonesia Medan, 2023)
Assets are important resources for a company or other agencies. One example that uses assets is the company PT Dosni Roha Medan Branch. PT Dosni Roha Medan Branch has so far owned company assets with a data collection process carried out manually. To support company performance, an inventory of assets is needed to be used for work, such as office equipment, laptops/PCs, printers and vehicles. This research uses the waterfall method, UML, PHP, MySQL and CSS programming languages. The aim of this research is to make it easier for the company PT Dosni Roha Medan Branch in processing website-based asset inventory data. The results of this research provide information about the company's asset inventory, PT Dosni Roha, Medan Branch.